Vector Analysis of the Prayer Movement on Health Using Visual Media Multimedia Application Development Life Cycle - Indah Purnama Sari; Aulia Jannah; Abdillah Syahputra; Rivaldi Tanjung (Indonesian Journal of Education, Social Sciences and Research (IJESSR), 2021)
This study aims to determine the vector analysis in the prayer movement and to find out the benefits of the prayer movement on health using the visual media Multimedia Development Life Cycle (MDLC). The data collection technique uses the documentation method and data sources are obtained from primary data sources and secondary data (Qur'anic interpretation books, references related to vectors, prayer movements, health, previous research, articles, journals, and websites. Internet). The analysis technique used is deductive thinking techniques and maudhu'iy interpretation techniques. The results showed that: (1) According to a scientific perspective, vectors with the prayer movement can be added to a vector called the resultant vector obtained by several methods, namely the triangle method as well as bowing movements, the parallelogram method such as movement during prostration, the polygon method. the same is the case with bowing movements and movements towards i'tidal, and analytical calculations using the 2-way resultant formula. (2) According to the perspective of Al-Qur'an, when looking for the resultant force on a vector, it must be known the value and direction, namely the movement of one rakat prayer is equal to one 360 rotation. (3) The benefits of the prayer movement for health are that every movement that is correct and perfect and carried out continuously has many benefits that can be felt by the body.